Abnormal pinocytosis and valence-variable behaviors of cerium suggested a cellular mechanism for plant yield reduction induced by environmental cerium. (November 2017) - Wang, Lihong; He, Jingfang; Yang, Qing; Lv, Xiaofen; Li, Jigang; Chen, David D.Y.; Ding, Xiaolan; Huang, Xiaohua; Zhou, Qing
Abstract: The environmental safety of cerium (Ce) applications in many fields has been debated for almost a century because the cellular effects of environmental Ce on living organisms remain largely unclear. Here, using new, interdisciplinary methods, we surprisingly found that after Ce(III) treatment, Ce(III) was first recognized and anchored on the plasma membrane in leaf cells. Moreover, some trivalent Ce(III) was oxidized to tetravalent Ce(IV) in this organelle, which activated pinocytosis. Subsequently, more anchoring sites and stronger valence-variable behavior on the plasma membrane caused stronger pinocytosis to transport Ce(III and IV) into the leaf cells. Interestingly, a great deal of Ce was bound on the pinocytotic vesicle membrane; only a small amount of Ce was enclosed in the pinocytotic vesicles. Some pinocytic vesicles in the cytoplasm were deformed and broken. Upon breaking, pinocytic vesicles released Ce into the cytoplasm, and then these Ce particles self-assembled into nanospheres. The aforementioned special behaviors of Ce decreased the fluidity of the plasma membrane, inhibited the cellular growth of leaves, and finally, decreased plant yield. In summary, our findings directly show the special cellular behavior of Ce in plant cells, which may be the cellular basis of plant yield reduction induced by environmental Ce. Graphical abstract: Highlights: Ce(III) was first recognized and anchored on the plasma membrane in leaf cells. Some trivalent Ce(III) was oxidized to tetravalent Ce(IV) in the plasma membrane. Ce(III) activated pinocytosis of plant leaf cells. Abnormal pinocytosis and valence-variable behaviors of cerium reduced yield. Abstract : Abnormal pinocytosis and valence-variable behaviours of cerium suggested a cellular mechanism for plant yield reduction induced by environmental cerium.